A Comparison of the Physicochemical Properties and Fatty Acid Composition of Indaiá (Attalea dubia) and Babassu (Orbignya phalerata) Oils - Silva Ferreira, Bianca (The Scientific World Journal, 2012)
The physicochemical properties and fatty acid composition of Attalea dubia (Mart.) Burret (indaiá) seed oil were investigated. The oil was extracted in a soxhlet apparatus using petroleum ether and evaluated for iodine, acid, peroxide, ester, and saponification values. The oil was also analyzed using infrared and nuclear magnetic resonance spectroscopy. The fatty acid profile of the oil was determined by GC-MS. For each analysis indaiá oil was compared to Orbignya phalerata (babassu) oil. The two oils appeared to be very similar in their fatty acid composition, in which lauric acid (the most abundant), myristic acid, caprylic acid, and capric acid were the four main fatty acids detected. The unsaturated fatty acids content was lower for indaiá oil (5.8%) than for babassu oil (9.4%). The results suggest that indaiá palm tree could be cultivated as a new source of vegetable oil with potential for food and cosmetic industries.